Accuracy of three image techniques of measurement from cemento-enamel junction to alveolar crest in relation to clinical attachment level - Rios, Marcelo de Azevedo; Rios, Jacqueline Machado Gurjão; Rubira, Izabel Regina Fischer (Revista de Ciências Médicas e Biológicas, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; text-autospace:ideograph-other; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman"; mso-fareast-language:EN-US;} --> <!--[endif] --> This research aimed to determine the comparison, correlation and accuracy of three radiographic methods and one clinical method for measuring the distance between cemento-enamel junction and the alveolar crest in lower molars and bicuspids in patients with periodontal bone loss, who underwent clinical probing and vertical bite-wing radiographs. Only areas with probing depth greater or equal to 5 mm were included in the sample. The distance between cemento-enamel junction and the apical portion of 82-bone defect was verified through double-needle compass, digital caliper and the software Dentscan Dentview. The accuracy, correlation and comparison between clinical and radiological variables were recorded. The results showed that when the attachment level was the gold standard, the double-needle compass expressed the best accuracy (71% of sensitivity and 84.5% of specificity), followed by digital caliper (0% of sensitivity and 82.8% of specificity) and Dentscan Dentview (0% of sensitivity and 75.9% of specificity) regardless of testing variable or gold standard’s location, more severe diseases were underestimated than overestimation of onset disease. The systems with digital resources showed greater measurement values than methods without digital resources. All the variables presented.